The comparative statics of effective demand - Jochen Hartwig (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2017)
Keynes introduces the term 'effective demand' in chapter 3 of the General Theory as designating the point of intersection of two functions: the 'aggregate demand function' (D) and the 'aggregate supply function' (Z). For the first time in the literature, I here specify exact functional forms for the D and Z functions and run numerical simulations which allow to study the comparative statics of the model in the face of various 'shocks'. The demonstration of how the D/Z model actually works will hopefully prove useful for future students of the economics of Keynes.
Keywords: B31; E12; 330; Keynes; effective demand; D/Z model